2014
DOI: 10.1002/jor.22677
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of beta‐catenin signaling by Pb leads to incomplete fracture healing

Abstract: There is strong evidence in the clinical literature to suggest that elevated lead (Pb) exposure impairs fracture healing. Since Pb has been demonstrated to inhibit bone formation, and Wnt signaling is an important anabolic pathway in chondrocyte maturation and endochondral ossification, we investigated the impact of Wnt therapy on Pb-exposed mice undergoing bone repair in a mouse tibial fracture model. We established that tibial fracture calluses from Pb-treated mice were smaller and contained less mineralized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 44 publications
0
17
0
1
Order By: Relevance
“…Secondly, accumulating evidence shows a critical role for the Wnt/β-catenin signaling pathway in bone mass homeostasis [ 2 ]. Recent studies reported that toxic mechanisms of Pb on bone inhibit Wnt/β-catenin [ 37 , 38 ] signaling, and a recent phase II trial of an antagonist of schlerostin, an inhibitor of Wnt signaling, demonstrated efficacy in increasing BMD (PMID: 25196993). However, more definitive mechanisms remain largely unknown, and very few studies have examined metal exposure as a biological mechanism of osteoporosis [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, accumulating evidence shows a critical role for the Wnt/β-catenin signaling pathway in bone mass homeostasis [ 2 ]. Recent studies reported that toxic mechanisms of Pb on bone inhibit Wnt/β-catenin [ 37 , 38 ] signaling, and a recent phase II trial of an antagonist of schlerostin, an inhibitor of Wnt signaling, demonstrated efficacy in increasing BMD (PMID: 25196993). However, more definitive mechanisms remain largely unknown, and very few studies have examined metal exposure as a biological mechanism of osteoporosis [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bromoindirubin oxime (BIO; Sigma Aldrich Chemicals) or control vehicle was administered intraperitoneally into 8‐week‐old wild‐type male mice (0.75 mg·kg −1 IP 3 times over 9) . Mice were sacrificed at 1 day after last BIO injection.…”
Section: Methodsmentioning
confidence: 99%
“…BIO treatment also increased β-catenin staining to control levels ( 138 ), suggesting Wnt involvement. Indeed, BIO has been shown to induce CXCL12 expression in mouse tibial fracture callus ( 139 ). The Beier study suggests that lead may in part impact fracture repair by reducing CXCL12/CXCR4-mediated progenitor cell recruitment to the site of injury.…”
Section: Metalsmentioning
confidence: 99%